The mechanism of rotational movement generation during a round-off in gymnastics on the floor - Asano, Y.; Fujita, Z.; Tsuchiya, J. (Japan Journal of Physical Education, Health and Sport Sciences, 2024)
Round-off is essential for performing backward somersaults on the gymnastics floor; however, very few studies have focused on angular momentum generation during a round-off. This study aimed to describe the generation mechanism of rotational movement during round-off. Eight male gymnasts performed a round-off to a stretched backward somersault from a one-leg standing position. Each trial was videotaped using four cameras to obtain the three-dimensional coordinate data. A 14-segment link model was used to examine the total-body potential energy, kinetic energy, and angular momentum of the somersault and twist axes. The joint forces and torques were calculated using inverse dynamics. The main results are as follows: